Hikeshi modulates the proteotoxic stress response in human cells: Implication for the importance of the nuclear function of HSP70s. (5th October 2017) - Rahman, Khondoker Md Zulfiker; Mamada, Hiroshi; Takagi, Masatoshi; Kose, Shingo; Imamoto, Naoko
Abstract : Hikeshi mediates the heat stress‐induced nuclear import of heat‐shock protein 70 (HSP70s: HSP70/HSC70). Dysfunction of Hikeshi causes some serious effects in humans; however, the cellular function of Hikeshi is largely unknown. Here, we investigated the effects of Hikeshi depletion on the survival of human cells after proteotoxic stress and found opposite effects in HeLa and hTERT‐RPE1 (RPE) cells; depletion of Hikeshi reduced the survival of HeLa cells, but increased the survival of RPE cells in response to proteotoxic stress. Hikeshi depletion sustained heat‐shock transcription factor 1 (HSF1) activation in HeLa cells after recovery from stress, but introduction of a nuclear localization signal‐tagged HSC70 in Hikeshi‐depleted HeLa cells down‐regulated HSF1 activity. In RPE cells, the HSF1 was efficiently activated, but the activated HSF1 was not sustained after recovery from stress, as in HeLa cells. Additionally, we found that p53 and subsequent up‐regulation of p21 were higher in the Hikeshi‐depleted RPE cells than in the wild‐type cells. Our results indicate that depletion of Hikeshi renders HeLa cells proteotoxic stress‐sensitive through the abrogation of the nuclear function of HSP70s required for HSF1 regulation. Moreover, Hikeshi depletion up‐regulates p21 in RPE cells, which could be a cause of its proteotoxic stress resistant. Abstract : We found that Hikeshi is required for the survival of HeLa cells in response to proteotoxic stress, but depletion of Hikeshi increases the survival of hTERT‐RPE1 cells. Depletion of Hikeshi renders HeLa cells proteotoxic stress‐sensitive through the abrogation of the nuclear function of HSP70s required for HSF1 regulation. In addition, we found Hikeshi‐depleted hTERT‐RPE1 upregulates p21, which could be one cause of its proteotoxic stress resistance.